1964
DOI: 10.1084/jem.120.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterial Pseudotuberculosis in Mice

Abstract: Latent corynebactenai infection occurs naturally in many strains of mice. It can be evoked into the active disease, pseudotuberculosis, by a single injection of 10 mg of cortisone. The cortisone effect was tested in 21 colonies, representing 11 genetically different strains of mice. Animals of the C57B1/6, DBA/2, and RIII strains were shown to be latently infected with Corynebacterium kutscheri by the fact that they developed fatal pseudotuberculosis following cortisone treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Remarkably few challenge organisms were detected in the kidneys of mice immunized with strain CM23Fdr. DISCUSSION We have shown that in general the susceptibilities of the two mouse strains were as described nearly 10 years earlier Pierce-Chase et al 1964); Swiss Lynch mice were susceptible to virulent C. kutscheri infection whereas C57BI/6 mice were resistant. There was a difference of nearly 100-fold in LD 50 for C. kutscheri between the two parental strains; their Fl hybrid was intermediate.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…Remarkably few challenge organisms were detected in the kidneys of mice immunized with strain CM23Fdr. DISCUSSION We have shown that in general the susceptibilities of the two mouse strains were as described nearly 10 years earlier Pierce-Chase et al 1964); Swiss Lynch mice were susceptible to virulent C. kutscheri infection whereas C57BI/6 mice were resistant. There was a difference of nearly 100-fold in LD 50 for C. kutscheri between the two parental strains; their Fl hybrid was intermediate.…”
Section: Resultsmentioning
confidence: 53%
“…In a subsequent paper (Hirst & Olds, 1978) we present evidence that the avirulent organism is not a variant of C. kutscheri but a streptococcus of Group N. If these two organisms are unrelated how can one explain the previous reports Pierce-Chase et at. 1964) that cortisone evoked the clinical disease in mice given the alleged variant?…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations